COVID‐19 among health care workers and their impact on the health care system in a teaching hospital in Pakistan: A cross sectional observational study. Issue 1 (2nd December 2022) - Haq, Faiz Ul; Rahman, Saeed Ur; Imran, Muhammad; Romman, Muhammad; Shah, Asaf; Aslam, Zeenaf; Ullah, Farman; Madadi, Shekiba; Dino Steinmetz, Carl Hermann; Cuschieri, Sarah
Abstract: Background and Aims: Health care workers (HCWs) are thought to be high‐risk population for acquiring coronavirus disease (COVID‐19). The COVID‐19 emergence has had a profound effect on healthcare system. We sought to investigate the COVID‐19 among HCWs and their effects on the healthcare system. Methods: A cross sectional observational study was conducted at Timergara teaching hospital. The study included HCWs with positive real time polymerase chain reaction (Q‐PCR) for severe acute respiratory syndrome coronavirus (SARS‐CoV‐2). The study duration was from April to September, 2020. The demographic profile of each recruited subject was collected through structured interview. The patient's admissions to hospital were collected for the 5 months before (October 2019–February 2020) and 5 months after lockdown (March–July 2020). Results: A total of 72 out of 689 (10%) HCWs were tested positive for SARS‐CoV‐2, of whom 83% were front‐liners. The majority were male (72%), with comorbidities (14%) and no mortality. The structured interview of all participants showed that the healthcare setting was the major possible source of infection (97%). The patient admissions into the hospital were reduced by 42% during lockdown than prelockdown period. The patients admission was significantly decreased in the medical ward during lockdown (60% decrease; p  < 0.01) with slightly similar trends in other departments. Conclusion: In conclusion, we found increased risk of COVID‐19 for front‐line HCWs. Lack of mortality was the favorable outcome. Lack of replacing the infected HCWs possibly explained the marked decrease in hospital admissions, and potential inadequate healthcare delivery during the lockdown. Understanding SARS‐CoV‐2 among HCWs and their impact on health‐care system will be crucial for countries under COVID‐19 crises or in case of future pandemic to deliver proper health services.